MAXILLARY DISTOMOLARS AT PATIENTS WITHOUT ASSOCIATED SYNDROMES: A CASE REPORT - Carmen Gabriela Stelea; Ovidiu Ștefănescu; Alina Mateuță; Marius Enașoaie; Oana Elena Ciurcanu; Cristina Popa (Romanian Society of Oral Rehabilitation, 2018)
The distomolars are supernumerary teeth that forms behind of maxillary and mandibular third molars. The etiology of this numerary anomaly has multiple theories but none of them is fully accepted. Most of the time, supernumerary teeth are associated with genetics syndromes like labio-palatal cleft, cleidocranial dysostosis, Gardner syndrome, but at healthy patients the prevalence is very low. This study presents three cases diagnosticated at Hospital "Sf. Spiridon" Iasi, Oral and MaxilloFacial department, with maxillary distomolars at patients without any associated syndromes. The anomaly did not had local complications, it was diagnosticated following paraclinic exams like panoramic radiographs and cone-beam computer tomography.